Multi-level regulation of hindgut homeostasis by volatile fatty acid administration in dairy goats: linking microbial metabolism to epithelial inflammation and barrier function - Yongkang Zhen; Ali Rahmat; Chong Zhang; Jiaqi Lin; Jianjun Ma; Yuhong Zhong; Mengzhi Wang (mSystems, 2025)
ABSTRACT This study provided a comprehensive exploration of the nutritional regulation of volatile fatty acids (VFAs) on hindgut microbial metabolism and epithelial homeostasis in dairy goats. Twenty-four goats were orally administered sodium acetate (SA) at 0.8 g/kg of body weight (BW), propionate (SP) at 0.8 g/kg of BW, butyrate (SB) at 0.5 g/kg of BW, or saline (CON) before morning feeding for 12 days (n = 6/group). Serum and hindgut epithelial tissues were collected to measure antioxidant capacity, inflammatory cytokines, and tight junctions. Cecal contents were collected for 16S rRNA sequencing and metabolome analysis, and colonic epithelial cells were harvested for transcriptome sequencing. The data demonstrated that VFAs positively affected hindgut homeostasis. SB reduced serum malondialdehyde levels (P = 0.042), while SA and SP increased intestinal interleukin-10 concentration compared with CON (P < 0.001). All three VFAs enhanced gut barrier functions by increasing tight junctions compared with CON (P < 0.05). The data revealed distinct bacterial abundances and diversities associated with VFA administration, with notable responders including Rikenellaceae dgA-11 gut group, Christensenellaceae R-7 group, and Bacteroides. Metabolome analysis indicated significant changes in metabolic processes, such as purine, arachidonic acid, tyrosine, and tryptophan metabolism. Transcriptome analysis showed that SA and SP influenced endocrine and digestive functions, metal ion homeostasis, and muscle development in the colonic epithelium, with specific immune response pathways enriched in SB. Correlation analysis suggested interactions between hindgut bacteria and derived metabolites and epithelial homeostasis. In short, our study suggested potential strategies for improving gut health and overall well-being in goats through dietary interventions.IMPORTANCEThe volatile fatty acids (VFAs), mainly produced by rumen microbiota, play an important role in ruminal metabolic functions and epithelial health, but their impact on the hindgut has received limited attention. Our study highlighted the significant role of VFAs in hindgut bacterial metabolism and homeostasis, providing novel insights into the role of VFAs in regulating hindgut metabolism and physiological homeostasis beyond the rumen.